Best years : going to the movies, 1945-1946 - Affron, Charles (ACLS Humanities E-Book., 2009)
Best Years shines light on a critical juncture in American history and the history of American cinema̮the end of World War II (1945) and a year of unprecedented success in Hollywood's "Golden Age" (1946). This unique time provides a rich blend of cinema genres and types̮from the battlefront to the home front, the peace film to the woman's film, psychological drama, and the period's provocative new style, film noir. This book focuses on films that were famous, infamous, forgotten, and unforgettable, with big budget A-films, road shows, and familiar series share t.